Quantitative profiling of N6-methyladenosine at single-base resolution in stem-differentiating xylem of Populus trichocarpa using Nanopore direct RNA sequencing - Gao, Yubang; Liu, Xuqing; Wu, Bizhi; Wang, Huihui; Xi, Feihu; Kohnen, Markus V.; Reddy, Anireddy S. N.; Gu, Lianfeng (Genome Biology, 2021)
There are no comprehensive methods to identify N 6 -methyladenosine (m 6 A) at single-base resolution for every single transcript, which is necessary for the estimation of m 6 A abundance. We develop a new pipeline called Nanom6A for the identification and quantification of m 6 A modification at single-base resolution using Nanopore direct RNA sequencing based on an XGBoost model. We validate our method using methylated RNA immunoprecipitation sequencing (MeRIP-Seq) and m 6 A-sensitive RNA-endoribonuclease–facilitated sequencing (m6A-REF-seq), confirming high accuracy. Using this method, we provide a transcriptome-wide quantification of m 6 A modification in stem-differentiating xylem and reveal that different alternative polyadenylation (APA) usage shows a different ratio of m 6 A.